Advancing Islamic Knowledge Through The Da'wah of Women in Patriarchal Culture - Faizah, Faizah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article aims to describe the existence of women's da'wah amid the domination of master guru's da'wah in Sasak culture, which is patriarchal in advancing Islamic knowledge. This research was conducted in Mataram, West Nusa Tenggara, Indonesia. The study used qualitative descriptive methods, with data collection techniques through interviews, observation and documentation. The study found that patriarchal culture, including the religious sphere, influences the Sasak people's lives. The dominance of the Tuan guru in da'wah is seen in almost all contexts of da'wah. Da'wah is carried out routinely and incidentally through religious lectures in prayer rooms, mosques, religious, social organizations, government institutions and private institutions and is carried out by utilizing mass media. While women's da'wah through lectures has limited access, women preachers preach more in the women's community. In terms of quantity, the number of female preachers is very inadequate compared to the number of master teachers. The study also found that there is stigma and stereotypes of women in da'wah and marginalization of women in da'wah, which closes access for women to appear as preachers. Some female preachers seem and preach in the community because they have the support of their families.